Preparation method and application of porous adsorption material for trace odor purification with visual effect

By adding L-aspartic acid during Cu-BTC preparation, Cu2+~Asp@Cu-BTC composite adsorbent was prepared, which solved the problem that the existing adsorbent could not be intuitively judged after adsorbing trace amounts of methylsulfide and trimethylamine. The problem of adsorption conditions has achieved efficient adsorption and visual purification effects.

CN116237024BActive Publication Date: 2025-02-25GD MIDEA AIR CONDITIONING EQUIP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310070556.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-13
Publication Date
2025-02-25
Estimated Expiration
2043-01-13

AI Technical Summary

Technical Problem

The color of existing adsorbents remains unchanged after adsorbing traces of methylsulfide and trimethylamine. It is impossible to intuitively determine whether the adsorbent material is saturated or failed, and the adsorption efficiency is low.

Method used

The Cu2+~Asp@Cu-BTC composite adsorbent is prepared by a normal temperature stirring method to add L-aspartic acid to prepare Cu2+~Asp@Cu-BTC composite adsorbent. The material will undergo color changes after adsorbing methylsulfide and trimethylamine to achieve Visualization of adsorption purification effect.

Benefits of technology

Highly efficient adsorption of trace amounts of methylsulfide and trimethylamine is achieved, with the adsorption amount significantly higher than that of commercial activated carbon, and the state of the adsorbed material is intuitively judged through color changes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116237024B_ABST
    Figure CN116237024B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of indoor air purification, and specifically relates to a method and application of a porous adsorbent material for purifying trace odors with a visualization effect. The method comprises the following steps: after ZnO is mixed with water and ultrasonically dispersed, DMF is added and stirred to obtain a suspension A; copper salt and L-Asp are completely dissolved in water to obtain a solution B; trimesic acid is dissolved in anhydrous ethanol to obtain a solution C; the obtained solution is stirred and mixed and filtered to obtain a solid product; the solid product is soaked in methanol, centrifuged, dried, and finally vacuum degassed and activated to obtain a blue solid powder product. The composite adsorbent prepared by the present invention not only has an extremely high adsorption capacity for trace amounts of methyl sulfide and trimethylamine, but also the composite porous adsorbent material develops color after adsorbing methyl sulfide and trimethylamine, realizing the visualization of the adsorption and purification effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of indoor air purification, and in particular relates to a preparation method and application of a porous adsorption material for purifying trace odors with a visualized effect. Background Art

[0002] Modern independent and closed home environments have improved people's living experience, but various odors generated indoors are also more likely to gather and difficult to dissipate in time, resulting in a deteriorating indoor environment. The presence of various odors seriously interferes with people's lives, causing people to feel unhappy and disgusted, and at the same time poses a serious threat to physical health. Methyl sulfide and trimethylamine are two typical indoor odor substances. Their olfactory threshold and toxicity threshold are very low. They can make people uncomfortable at extremely low concentrations. Long-term contact can cause damage to the human respiratory system and nervous system. In severe cases, it can cause fetal malformation, human suffocation and even death. According to the standard method of odor pollution olfactory test in my country - the three-point comparison odor bag method (GB / T14675-93), the National Environmental Protection Key Laboratory for Odor Pollution Control measured the odor threshold of methyl sulfide to be only 0.002ppm, while the odor threshold of trimethylamine is as low as 0.0009ppm. Therefore, it is urgent to develop efficient and lasting indoor odor removal technology for efficient purification of trace methyl sulfide and trimethylamine odor gases and solve the pain point problem of difficult indoor odor removal.

[0003] At present, the mainstream methods for odor purification are: masking method, biodegradation method, absorption method, catalytic method and adsorption method. Among them, the adsorption method is one of the main odor removal technologies because of its advantages of high efficiency, simple equipment and low secondary pollution. The core of the adsorption method is the adsorption material. At present, the most widely used odor purification adsorption material is activated carbon, which has the advantages of high specific surface area, large pore volume and good stability. However, activated carbon often has a weak adsorption effect on these odorous gases, resulting in a small adsorption capacity for trace gases and low odor purification efficiency. For example, Esther et al. (Esther Vega, Jesús Lemusb, Alba Anfrunsa, Rafael Gonzalez-Olmosa, José, Palomarb, María J. Martin. Adsorption of volatile sulphur compounds onto modified activated carbons: Effect of oxygen functional groups [J]. Journal of Hazardous Materials, 2013. 258: 77-83.) used commercial activated carbon to oxidize with nitric acid and ozone, which increased the content of oxygen-containing functional groups on the surface of the activated carbon, thereby improving the adsorption of dimethyl sulfide by the activated carbon. The saturated adsorption capacity of dimethyl sulfide at an initial concentration of 4 ppm was 21 mg / g, an increase of 162.5%. Tesfay et al. (Tesfay Berhe, Gebreegziabher, ShuangWang, Hyungseok Namd. Adsorption of H2S, NH3 and TMA from indoor air using porous corncob activated carbon: Isotherm and kinetics study [J]. Journal of Environmental Chemical Engineering, 2019.7 (4): 103234.) used corncob activated carbon modified by impregnation with copper to significantly improve the adsorption performance of 400ppm trimethylamine in a closed room, and the maximum adsorption capacity reached 323.56mg / g. However, the above reports mainly focus on the adsorption and purification of higher concentrations of dimethyl sulfide and trimethylamine, and the removal of trace odors needs further study.

[0004] On the other hand, the color of the current mainstream adsorbents does not change significantly after absorbing odorous substances, which makes it difficult for consumers to intuitively judge whether the adsorbent material is saturated or needs to be replaced, which is also a pain point. Therefore, the preparation of a new adsorbent material with visual characteristics and high efficiency for adsorbing and purifying trace odorous gases such as dimethyl sulfide and trimethylamine has always been a hot issue that needs to be solved by technicians in this field. Summary of the invention

[0005] Based on the shortcomings of the prior art, the primary purpose of the present invention is to provide a method for preparing a porous adsorbent material with a visual effect for purifying trace odors. The present invention adopts a normal temperature stirring method to add a Cu-BTC in the process of preparing the Cu-BTC. 2+ Aspartic acid produces chelating effect, and one-step preparation of Cu 2+ The Asp@Cu-BTC composite adsorbent not only has an extremely high adsorption capacity for trace amounts of dimethyl sulfide and trimethylamine, but also the composite porous adsorbent material will show color after adsorbing dimethyl sulfide and trimethylamine, thus realizing the visualization of the adsorption and purification effect.

[0006] Another object of the present invention is to provide a porous adsorbent material for purifying trace odors with a visualized effect, which is prepared by the above method.

[0007] Another object of the present invention is to provide an application of the above-mentioned porous adsorption material for purifying trace odors with visualization effect.

[0008] The purpose of the present invention is achieved through the following technical solutions.

[0009] A method for preparing a porous adsorption material for purifying trace odors with a visual effect comprises the following steps:

[0010] (1) After ZnO and water are mixed and ultrasonically dispersed, N,N-dimethylformamide (DMF) is added and stirred to obtain suspension A; copper salt and L-aspartic acid (L-Asp) are completely dissolved in water to obtain solution B; trimesic acid is dissolved in anhydrous ethanol to obtain solution C;

[0011] (2) Pour the solution B obtained in step (1) into the suspension A, stir and mix evenly, then add the solution C and continue stirring, and filter to obtain a solid product;

[0012] (3) The solid product in step (2) is soaked in methanol, centrifuged, dried, and finally vacuum degassed and activated to obtain a blue solid powder product Cu 2+ ~Asp@Cu-BTC composite adsorbent.

[0013] Preferably, in step (1), the volume ratio of water in suspension A to water in solution B is 1:1.

[0014] Preferably, the volume ratio of the total amount of water in step (1):DMF:anhydrous ethanol is 1:1:1.

[0015] Preferably, the copper salt in step (1) refers to one of copper nitrate, copper sulfate, copper chloride, copper acetate and the like.

[0016] Preferably, the molar ratio of ZnO to copper salt in step (1) is 1:(1-3).

[0017] Preferably, the molar ratio of L-Asp to copper salt in step (1) is 1:(1.1-4.4).

[0018] Preferably, the stirring time in step (2) is 10 to 45 minutes.

[0019] Preferably, the drying in step (3) refers to drying at 80° C. for 4 to 6 hours.

[0020] Preferably, the temperature of the vacuum degassing activation in step (3) is 150° C. and the time is 4 to 8 hours; the pressure of the vacuum degassing activation is -0.08 to -0.1 MPa.

[0021] The trace odor purification porous adsorption material Cu with visual effect is prepared by the above method. 2+ ~Asp@Cu-BTC.

[0022] The above-mentioned porous adsorption material for purifying trace odors with visual effects can be used for adsorbing dimethyl sulfide and / or trimethylamine.

[0023] Compared with the prior art, the present invention has the following advantages and technical effects:

[0024] (1) The adsorbent of the present invention has an ultra-high content of metal active centers, so that it has excellent adsorption and purification performance for trace amounts of dimethyl sulfide and trimethylamine.

[0025] (2) The adsorbent of the present invention introduces L-aspartic acid, which can protect the skeleton of Cu-BTC and improve the water vapor stability of the material. On the other hand, the nitrogen oxide functional group of L-aspartic acid can further enhance its excellent adsorption effect on trace amounts of dimethyl sulfide and trimethylamine.

[0026] (3) Compared with the existing adsorbents, the adsorbent of the present invention has a penetration adsorption capacity of 91.00 and 46 mg / g at a concentration of 5 ppm of dimethyl sulfide and trimethylamine, respectively, which is much higher than 0.00 and 7.34 mg / g of commercial coconut shell CTC100 activated carbon.

[0027] (4) Compared with traditional adsorbents, the Cu 2+~ The Asp@Cu-BTC adsorbent changes color significantly after adsorbing dimethyl sulfide and trimethylamine, which makes it easy to visually judge whether the adsorption material has reached adsorption saturation failure.

[0028] (5) The preparation method of the present invention is simple, and a composite material can be obtained through a one-step synthesis. The raw materials are cheap, the production cost is low, and it is conducive to large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 X-ray diffraction patterns of L-Asp, Cu-BTC and materials obtained from various embodiments of the present invention.

[0030] Figure 2 The adsorption breakthrough curves of 5 ppm dimethyl sulfide by commercial coconut shell CTC100 activated carbon and the adsorbents obtained in various embodiments of the present invention are shown.

[0031] Figure 3 The adsorption breakthrough curves of 5 ppm trimethylamine by commercial coconut shell CTC100 activated carbon and the adsorbents obtained in various embodiments of the present invention.

[0032] Figure 4 This is a schematic diagram of the color change of the adsorbent obtained in Example 1 before and after adsorbing dimethyl sulfide or trimethylamine. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. The raw materials involved in the present invention can be purchased directly from the market. For process parameters not particularly noted, conventional techniques can be used.

[0034] Example 1

[0035] (1) ZnO (0.293 g) was mixed with deionized water (8 mL), and after ultrasonic dispersion for 15 min, DMF (16 mL) was added and stirred to obtain a ZnO suspension; Cu(NO3)2·3H2O (1.74 g) and L-Asp (0.288 g) were completely dissolved in deionized water (8 mL) to obtain a mixed solution of Cu(NO3)2 and L-Asp; trimesic acid (0.84 g) was dissolved in anhydrous ethanol (16 mL) to obtain a trimesic acid solution;

[0036] (2) Pour the mixed solution of Cu(NO3)2 and L-Asp obtained in step (1) into the ZnO suspension, keep stirring and mixing evenly, then add the trimesic acid solution and continue stirring for 15 minutes, and obtain a light blue solid product after filtering;

[0037] (3) The solid product in step (2) was soaked in methanol, centrifuged, dried, and then vacuum degassed and activated at 150°C for 6 h to obtain a blue solid powder composite adsorbent, denoted as Cu 2+ ~Asp@Cu-BTC-1.

[0038] Example 2

[0039] (1) ZnO (0.586 g) was mixed with deionized water (8 mL), and after ultrasonic dispersion for 15 min, DMF (16 mL) was added and stirred to obtain a ZnO suspension; Cu(NO3)2·3H2O (1.74 g) and L-Asp (0.218 g) were completely dissolved in deionized water (8 mL) to obtain a mixed solution of Cu(NO3)2 and L-Asp; trimesic acid (0.84 g) was dissolved in anhydrous ethanol (16 mL) to obtain a trimesic acid solution;

[0040] (2) Pour the mixed solution of Cu(NO3)2 and L-Asp obtained in step (1) into the ZnO suspension, keep stirring and mixing evenly, then add the trimesic acid solution and continue stirring for 30 minutes, and obtain a light blue solid product after filtering;

[0041] (3) The solid product in step (2) was soaked in methanol, centrifuged, dried, and then vacuum degassed and activated at 150°C for 4 h to obtain a blue solid powder composite adsorbent, denoted as Cu 2+ ~Asp@Cu-BTC-2.

[0042] Example 3

[0043] (1) ZnO (0.193 g) was mixed with deionized water (8 mL), and after ultrasonic dispersion for 15 min, DMF (16 mL) was added and stirred to obtain a ZnO suspension; Cu(NO3)2·3H2O (1.74 g) and L-Asp (0.435 g) were completely dissolved in deionized water (8 mL) to obtain a mixed solution of Cu(NO3)2 and L-Asp; trimesic acid (0.84 g) was dissolved in anhydrous ethanol (16 mL) to obtain a trimesic acid solution;

[0044] (2) Pour the mixed solution of Cu(NO3)2 and L-Asp obtained in step (1) into the ZnO suspension, keep stirring and mixing evenly, then add the trimesic acid solution and continue stirring for 45 minutes, and obtain a light blue solid product after filtering;

[0045] (3) The solid product in step (2) was soaked in methanol, centrifuged, dried, and then vacuum degassed and activated at 150° C. for 8 h to obtain a blue solid powder composite adsorbent, denoted as Cu 2+~Asp@Cu-BTC-3.

[0046] The Cu-BTC and the composite adsorbents obtained in Examples 1 to 3 were characterized using a D8 Advance X-ray diffractometer from Bruker, Germany. Figure 1 The results showed that Cu 2+ The characteristic diffraction peaks of Cu-BTC not only appeared at 2θ=6.8°, 9.6° and 11.8° for Cu-Asp@Cu-BTC, but also the characteristic diffraction peaks of L-Asp did not appear. The structure of the adsorbent prepared on the surface was similar to that of Cu-BTC, and no L-Asp was deposited in the pores. 2+ ~Asp@Cu-BTC also showed new characteristic diffraction peaks at 2θ=5.5°, 11.06°, 14.66°, 19.78° and 26.58°. These characteristic peaks are consistent with those of Asp amino acid and Cu 2+ The characteristic diffraction peaks of the complexes are basically consistent, indicating that the material prepared by the present invention is Cu 2+ ~ Composite materials of Asp complex and Cu-BTC.

[0047] The outlet methyl sulfide concentration was detected by 456-GC gas chromatograph and pulsed flame photometric detector (PFPD). The stainless steel packed column was filled with a uniformly mixed adsorbent (10 mg) and quartz sand (80-120 mesh, 60 mg), and the packed column length was 5 mm. Nitrogen was used as the carrier gas, and a six-way valve was used for injection. The injection gas was dimethyl sulfide gas with a concentration of 5 ppm and a flow rate of 500 mL / min. The carrier gas flow rate was 10 ml / min, the column temperature was 373 K, and the detector temperature was 523 K.

[0048] Depend on Figure 2 It can be seen that for the dimethyl sulfide gas with a concentration of 5 ppm, the Cu 2+ The breakthrough points (20 ppb) of the permeation curves on Asp@Cu-BTC appeared at 131.3 min, 122.2 min and 143.0 min, respectively, and the penetration adsorption capacities were 91 mg / g, 85 mg / g and 99 mg / g, respectively, indicating that the Cu prepared in each example 2+ ~Asp@Cu-BTC has an excellent purification effect on trace dimethyl sulfide, and its adsorption capacity is significantly higher than that of CTC100 coconut shell activated carbon.

[0049] The outlet trimethylamine concentration was detected using a GC6600 gas chromatograph and a hydrogen flame ionization detector (FID). The stainless steel filling column is filled with a uniformly mixed adsorbent (10 mg) and quartz sand (80-120 mesh, 60 mg), and the filling column length is 5 mm. Nitrogen is used as the carrier gas, and a six-way valve is used for sample injection. The injection gas is trimethylamine gas with a concentration of 5 ppm and a flow rate of 500 mL / min. The carrier gas flow rate is 18.5 ml / min, the chromatographic column temperature is 423 K, and the detector temperature is 473 K. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the protection scope of the present invention.

[0050] Depend on Figure 3 It can be seen that for trimethylamine gas with a concentration of 5 ppm, the Cu 2+ The penetration points (0.5 ppm) of the penetration curve on Asp@Cu-BTC appeared at 70.0 min, 61.9 min and 64.9 min, respectively, and the penetration adsorption capacities were 46 mg / g, 41 mg / g and 43 mg / g, respectively, indicating that the Cu prepared in Example 1 2+ ~Asp@Cu-BTC-1 also has a good purification effect on trace trimethylamine, and its adsorption capacity is significantly higher than that of CTC100 coconut shell activated carbon.

[0051] Depend on Figure 4 It can be seen that for the composite Cu adsorbed with dimethyl sulfide or trimethylamine 2+ ~Asp@Cu-BTC undergoes an obvious color change, and the adsorbent changes from the original blue to blue-green, and the changes in the adsorption and purification process can be intuitively seen.

[0052] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. Application of a porous adsorbent material for purifying trace odors with a visual effect in the adsorption of dimethyl sulfide and / or trimethylamine, characterized in that: The trace odor purification porous adsorption material with visualization effect is prepared by the following steps: (1) After ZnO and water are mixed and ultrasonically dispersed, N, N-dimethylformamide is added and stirred to obtain suspension A; copper salt and L-aspartic acid are completely dissolved in water to obtain solution B; trimesic acid is dissolved in anhydrous ethanol to obtain solution C; (2) Pour the solution B obtained in step (1) into the suspension A and stir to mix evenly, then add the solution C and continue stirring, and obtain a solid product by filtering; (3) The solid product in step (2) is soaked in methanol, centrifuged, dried, and finally vacuum degassed and activated to obtain a blue solid powder product Cu 2+ ~Asp@Cu-BTC is the porous adsorption material for purifying trace odors with visual effects.

2. The use according to claim 1, characterized in that: In step (1), the volume ratio of water in suspension A to water in solution B is 1:

1.

3. The use according to claim 1, characterized in that: The volume ratio of the total amount of water in step (1): N, N-dimethylformamide: anhydrous ethanol is 1:1:

1.

4. The use according to claim 1, characterized in that: The copper salt in step (1) refers to one of copper nitrate, copper sulfate, copper chloride and copper acetate.

5. The use according to claim 1, characterized in that: The molar ratio of ZnO to copper salt in step (1) is 1:(1-3); The mass ratio of L-aspartic acid to copper salt in step (1) is 1:(1.1-4.4).

6. The use according to claim 1, characterized in that: The stirring time in step (2) is 10 to 45 min.

7. The use according to claim 1, characterized in that: The drying in step (3) refers to drying at 80° C. for 4 to 6 hours.

8. The use according to claim 1, characterized in that: The temperature of the vacuum degassing activation in step (3) is 150°C, and the time is 4 to 8 hours; the pressure of the vacuum degassing activation is -0.08 to -0.1 MPa.

Citation Information

Patent Citations

  • Formulation and process for CO2 capture using amino acids and biocatalysts

    CN102548644A

  • Amino acid @Cu-BTC composite adsorbent and preparing method thereof

    CN108339522A